Preface: Proceeding of Joint Conference on Green Engineering Technology & Applied Computing 2020 (IOP conference series. Materials Science and Engineering, 2020)
This joint conference is organized simultaneously of International Conference on Green Engineering & Technology 2020 (IConGETech2020) and International Conference on Applied Computing 2020 (ICAC2020). This joint conference invites papers from various fields in both green engineering & technology and applied computing related fields. The primary goal of the conference is to provide the opportunities for academicians, professionals, practitioers and policy makers in the engineering and computing fields to share their thoughts and empirical works both to those involved in their field or those interested in the subject being researched. The objectives of this Joint conference are: 1. To provide a forum for researchers, educators, students and industries to share and exchange ideas and research findings in both fields of researches. 2. To give an opportunity to both academia and industries to communicate on problems faced in current research and the industries. 3. To create networks and stimulate potential collaborations between researchers in the same field of research. International Conference on Green Engineering & Technology 2020 (IConGETech2020) will foster the progress in green engineering and related technology by contributing your expertise to what promises to be a very comprehensive and exciting meeting. The aim of the IConGETech2020 is exploring the advances and challenges in Green Engineering & Technology between academia, scientists and engineers by bringing together again the world class researchers and Industrial heads to discuss the latest developments and innovations in the fields of related field of research works. International Conference on Applied Computing 2020 (ICAC2020) aims to address the main issues of concern within the applied computing area and related fields. This conference offers a great opportunity to bring together professors, researchers, and scholars around the globe, having a great platform to deliver the latest innovative research result and the most recent development and trends in applied computing. We cordially invite all prospective authors to submit their original manuscripts to ICAC2020.